Broadband and Dual-Polarized Terahertz Wave Anomalous Refraction Based on a Huygens’ Metasurface - Ran, Jia; Xie, Mingli; Wen, Dandan; Zhang, Xiaolei; Xue, Chunhua (Frontiers in Materials, 2022)
Terahertz wavefront manipulation is one of the key terahertz technologies. While few of the research works on terahertz wavefront manipulation has broadband and dual-polarized responses. Here a broadband dual-polarized Huygens’ metasurface is proposed to realize high efficient terahertz wave anomalous refraction. By constructing simultaneous electric and magnetic responses in a bi-layer metasurface to produce Huygens’ resonance, broadband and large phase changes for dual-polarized terahertz wave are achieved. A phase change over 300° with transmission magnitude beyond 0.75 is realized between 0.4 THz and 1 THz. An array made of the metasurface with phase gradient is designed to achieve a 14.0° anomalous refraction for two orthogonal linear polarized waves at 0.93 THz. The structure consists of only two metal layers, providing a simple and high-efficiency design scheme for achieving efficient dual-polarized terahertz wavefront manipulation.